Nilai Pendidikan Islam Dalam Sistem Perkaderan Lembaga Kemahasiswaan Intra Kampus - Pribadi, Imam; Makmur (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2025)
This research examines the values ??of Islamic education embedded in the cadre system of intra-campus student organizations. The aim of this research is to identify main Islamic values, understand their implementation, and evaluate the effectiveness of the cadre process in forming Islamic character in students. This research uses a qualitative descriptive method with data collection techniques in the form of document analysis, interviews, and observation. The data obtained was analyzed thematically to identify patterns related to the values ??of Islamic education in the cadre system. The research results show that Islamic educational values ??such as faith, knowledge, and noble morals are explicitly or implicitly integrated into the cadre system. These values ??are instilled through religious character development, habituation to worship, and thematic discussions that strengthen students' understanding of Islamic teachings. Intensive assistance by senior members also supports this process. The findings show that this cadre system has a positive influence on the development of students' morals, integrity, and leadership qualities based on spiritual values. This research concludes that the integration of Islamic educational values ??in the student cadre system significantly contributes to forming strong character and leadership potential. Further research can explore more contextual and adaptive approaches to improving the cadre system in accordance with the evolving needs of students.